Effect of modified atmosphere packaging on the antioxidant potential of capsicum leaves - Borazon, Elaine Quintana (2005)
ABSTRACT The antioxidant activity of leaf extracts from Capsicum frutescens Linn. (var. Tabasco) was evaluated. This was done with the use of sulfite-induced peroxidation in an emulsified soybean oil system, which was evaluated and optimized in the process. Peroxide levels were monitored with the ferrous thiocyanate assay. Capsicum leaf extracts consistently inhibited sulfite-induced autoxidation of soybean oil as evidenced by a decrease in peroxides. On the average, these extracts, when added at concentrations equivalent to 0.20g f.wt./ml effected 42.7% inhibition relative to mixtures without antioxidant. This inhibition was lost after the leaves were subjected to modified atmosphere storage. The optimized system used for measuring the inhibitory effect of Capsicum leaf extracts on sulfite-induced lipid peroxidation provided a rapid method for evaluating antioxidant potential. The apparently anomalous pro-oxidant effect obtained with butylated hydroxytoluene, however, needs further study.